PROFIL ASAM AMINO DAN ASAM LEMAK IKAN LUNDU (Macrones gulio) - Susi Lestari; Mutiara Mutiara; Herpandi Herpandi; Dwi Inda Sari; Wulandari Wulandari (Marinade, 2023)
Macrones gulio is a type of fish that lives on the bottom of the waters (demersal), including the catfish species. Information on the nutritional content of fish is very important to study. The purpose of this study was to determine the amino acid, fatty acid and mineral (calcium and phosphorus) composition of the Macrones gulio. The method used in this research is laboratory experimental, with 4 treatment levels, namely whole fish, fillets with skin, head, fins and bones. The parameters observed in this research were amino acid profiles, fatty acid profiles and minerals. The results of the study showed that the highest amino acid in whole parts, heads, bones and fins was glycine and glutamic acid in fillets with skin. The lowest amino acid composition in each part of the fish body is the same, namely the amino acid hisitidine. The total fatty acids in the intact preparation were 26 types of fatty acids. Fillet with skin as much as 28 types of fatty acids. There are 36 types of fatty acids in the head and 38 types of fatty acids in the bones and fins. The highest content of calcium and phosphorus was found in the treatment of bones and fins and the treatment of the head, while the lowest content was found in the treatment of fillets and skin.